Ambipolar transport in Ni-catalyzed InGaAs nanowire field-effect transistors for near-infrared photodetection. (13th January 2021) - Guo, Yanan; Liu, Dong; Miao, Chengcheng; Sun, Jiamin; Pang, Zhiyong; Wang, Peng; Xu, Mingsheng; Han, Ning; Yang, Zai-Xing
Abstract: Weak n-type characteristics or poor p-type characteristics are limiting the applications of binary semiconductors based on ambipolar field-effect transistors (FETs). In this work, a ternary alloy of In0.2 Ga0.8 As nanowires (NWs) is successfully prepared using a Ni catalyst during a typical solid-source chemical-vapor-deposition process to balance the weak n-type conduction behavior in ambipolar GaAs NWFETs and the poor p-type conduction behavior in ambipolar InAs NWFETs. The presence of ambipolar transport, contributed by a native oxide shell and the body defects of the prepared In0.2 Ga0.8 As NWs, is confirmed by the constructed back-gated NWFETs. As demonstrated by photoluminescence, the bandgap of the prepared In0.2 Ga0.8 As NWs is 1.28 eV, offering the promise of application in near-infrared (NIR) photodetection. Under 850 nm laser illumination, the fabricated ambipolar NWFETs show extremely low dark currents of 50 pA and 0.5 pA when positive and negative gate voltages are applied, respectively. All the results demonstrate that with careful design of the surface oxide layer and the body defects, NWs are suitable for use in next-generation optoelectronic devices.